2021
DOI: 10.1108/intr-08-2020-0460
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumers' response to text-based chatbots in e-commerce: the moderating role of task complexity and chatbot disclosure

Abstract: PurposeArtificial intelligence (AI)-based chatbots have brought unprecedented business potential. This study aims to explore consumers' trust and response to a text-based chatbot in e-commerce, involving the moderating effects of task complexity and chatbot identity disclosure.Design/methodology/approachA survey method with 299 useable responses was conducted in this research. This study adopted the ordinary least squares regression to test the hypotheses.FindingsFirst, the consumers' perception of both the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 86 publications
(140 reference statements)
3
51
0
1
Order By: Relevance
“…Eren (2021) demonstrated that perceived trust in a bank's chatbot significantly affected customer satisfaction from chatbot use. Cheng et al (2021) found that users' trust in textbased chatbots in e-commerce will influence their reliance on the chatbot. In summary, trust will be one of the key factors influencing usage intention and customer attitude in chatbot context.…”
Section: User Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Eren (2021) demonstrated that perceived trust in a bank's chatbot significantly affected customer satisfaction from chatbot use. Cheng et al (2021) found that users' trust in textbased chatbots in e-commerce will influence their reliance on the chatbot. In summary, trust will be one of the key factors influencing usage intention and customer attitude in chatbot context.…”
Section: User Interfacementioning
confidence: 99%
“…Concerning the factors of positive attitude, trust and satisfaction will be the main factors of online behaviors in the chatbot context (Rajaobelina et al, 2021;Cheng et al, 2021;Nguyen et al, 2021). Previous research indicated that trust could be an affective attitude (Jones, 1996).…”
Section: Proposed Hypothesesmentioning
confidence: 99%
“…Another promising research area is the comparison of speech-based, text-based, and human interactions, in particular the impact of disclosing the CA's non-human identity. While this topic has already received initial attention for text-based CA interactions (Cheng et al, 2021;Mozafari et al, 2021aMozafari et al, , 2021b, it becomes progressively important given the increasing naturalness of synthetic speech output.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Particularly, in five studies combined theories have been used (TAM and DOI; TAM and ECM and ISS; TAM & SST; TAM, DOI and TOE) [1,29,35,37,40], whereas in seven (18%) research papers information system (IS) continuance models such as SOR, U&G, TPB, CAT, TRA, SERVQUAL, extended post acceptance model were applied. Cheng et al [52] used SOR theory to explain the behavior of consumers toward chatbots in the context of e-commerce.…”
Section: Behavioral Theoriesmentioning
confidence: 99%